Beliefs and behavior of Malaysia undergraduate female students in a public university toward breast self-examination practice - Akhtari-Zavare, Mehrnoosh; Juni, Muhamad Hanafiah; Md Said, Salmiah; Ismail, Irmi Zarina (Asian Pacific Organization for Cancer Prevention, 2013)
Background: Breast cancer is the most common cancer and the second principal cause of cancer deaths among women worldwide, including Malaysia. Methods: A cross-sectional study was carried out among 262 female undergraduate students in University Putra Malaysia using a validated questionnaire which was developed for this study. Results: The mean age of respondents was years. Most of them were single (83.1%), Malay (42.3%) and 20.7% reported having a family history of breast cancer. Eighty-seven (36.7%) claimed they had practiced BSE. Motivation and self-efficacy of the respondents who performed BSE were significantly higher compared with women who did not (p<0.05).There was no association between BSE practice and demographic details (p<0.05). Logistic regression analysis indicated that women who perceived greater motivation (OR=1.089, 95%CI: 1.016-1.168) and had higher confidence of BSE (OR=1.076, 95%CI: 1.028-1.126) were more likely to perform the screening. Conclusions: The findings show that Malaysian young female's perception regarding breast cancer and the practice of BSE is low. Targeted education should be implemented to improve early detection of breast cancer.